2015
DOI: 10.1002/anie.201411994
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(III)‐Catalyzed Directed CH Coupling with Diazo Compounds: Straightforward Access towards Extended π‐Systems

Abstract: The first highly efficient and scalable cobalt-catalyzed directed C-H functionalization with carbene precursors is presented. This methodology provides a modular route towards a new class of conjugated polycyclic hydrocarbons with tunable emission wavelengths both in solution and in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(109 citation statements)
references
References 99 publications
4
105
0
Order By: Relevance
“…[3g,i, 4] However,m ore recently the importance of high-valent Co III -catalyzed chelate-assisted CÀHb ond functionalizations withouta ny base or reductant have been demonstrated by Glorius, Ackermann, Ellman, and Chang following pioneering work by Matsunaga and Kanai. [5] Isoquinolinesa re found in many pharmaceuticals and biologicallya ctive alkaloids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3g,i, 4] However,m ore recently the importance of high-valent Co III -catalyzed chelate-assisted CÀHb ond functionalizations withouta ny base or reductant have been demonstrated by Glorius, Ackermann, Ellman, and Chang following pioneering work by Matsunaga and Kanai. [5] Isoquinolinesa re found in many pharmaceuticals and biologicallya ctive alkaloids.…”
mentioning
confidence: 99%
“…Use of 10 mol %o ft he Cp*Co III catalyst using MeOH or EtOH as solvent did not promote the reaction of oxime 1a with tolane (2a)( entries 1a nd 2). Changeo fs olvent and increasing the temperature moderately improves the yield (entries [3][4][5]. While employing 2,2,2-trifluoroethanol (TFE) as solventa t1 20 8Cs ignificantly improves the yield of 3aa (65 %; entry 5).…”
mentioning
confidence: 99%
“…In addition, pyridines with both donating and withdrawing groups also showed a broad functional group compatible to obtain the coupling products in good to excellent yields. In 2015, Feng et al reported another methodology using Pd(II)-catalyzed orthoacylation of 2-aryl pyridines (3) with arylglycines (88). Authors used Cu(OAc) 2 and K 2 S 2 O 8 to afford benzophenones (89) in the reaction.…”
Section: Reviewsmentioning
confidence: 99%
“…[88] Furthermore, this facile synthetic approach resulted in the discovery of a new family of extended p-systems. For the coupling of 2-phenyl pyridine (3) with dimethyl diazomalonate, the catalyst loading could be further decreased to 1 mol% without a significant decrease in yield.…”
Section: Coupling Of 2-aryl Pyridines and Alcoholsmentioning
confidence: 99%
“…[4] Although other metals have emerged as potentially useful catalysts for this type of transformation, [5][6][7][8][9][10] the use of palladium has been restricted to ac ouple of examples of a-diazo b-ketoester insertion into C(sp 2 )ÀH bonds. [11,12] This fact is highly surprising if we take into account the great success of Pd catalysis in cross-coupling reactions of diazo compounds with either organic halides or arylboronic acids.…”
mentioning
confidence: 99%